Representing Condomless Anal Sex: BAREBACKING, BUGCHASING AND AN AUSTRALIAN CASE OF CRIMINAL EXPOSURE TO HIV. - Kagan, Dion (AntiTHESIS, 2009)
The article examines the representation of condomless, anal sex between men as portrayed in mainstream Australian media coverage, such as the media's use of the terminology to describe the sexual acts between these men as "barebacking" and "bugchasing." Topics include an overview of a high-profile criminal case involving Australian Michael Neal, who was charged with knowingly attempting to infect men with the HIV virus, to illustrate the author's argument regarding language and culture.